Chelation, Characterization and Antimicrobial Screening of Some Mixed Antituberculosis–Vitamin Metal Drug Complexes - Bamigboye, M.O.; Obaleye, J.A.; Lawal, A.; Babamale, H.F.; Ajibola, A.A.; Adimula, V.O.; Lawal, M. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
In this study, mixed Zn(II), Cu(II), Co(II) complexes of Isoniazid and vitamin C were synthesized and characterized bymelting point, conductivity measurement, Fourier Transform Infra-red (FT-IR), Atomic Absorption Spectroscopy andelemental analyses. The bonding nature of the mixed parent ligands and the structure of the complexes were based onanalytical and spectroscopic techniques. The complexes were proposed to have the formula [M1L1L2(Cl2)],[M2L1L2(SO4)], [M3L1L2(Cl2)] where M1 = Zn(II), M2 = Cu(II), M3= Co (II) L1= Isoniazid and L2 = Vitamin C. Theinfra-red data relate to the results of the most informative and indicative region. The result of spectra data confirmed thatthe two ligands were bidentate in their mode of coordination with the metal ions. The complexes are in octahedralgeometry and the molar conductance was found to be non-electrolytic in nature. Antimicrobial test was carried outagainst four bacterial species namely Bacillus subtilus, Staphylococuss aureus, Escherichia coli and Pseudomonasaeroginosa. All the complexes showed higher antibacterial activity at the same concentration against the microorganismsused compared to the ligands.